O jogo tradicional nas aulas de Educação Física no ensino médio: experiências pedagógicas - Patias, Bhianca Conterato (2018)
This research deals with the Traditional Games as a playful manifestation expressed culturally and historically, related to the High School of Basic Education. It aims to analyze the pedagogical experiences developed with the Traditional Games as content of the curriculum component Physical Education in High School. More specifically, it aims to carry out pedagogical experiences with the Traditional Game in Secondary School and to understand the conception of the students and the teacher regent of the class, from the pedagogical experience with Traditional Games in Physical School Education (EFE). The research was carried out in a State school of the Municipality of Jaguari, in the interior of Rio Grande do Sul, with classes of 1st, 2nd and 3rd years of High School, through a participant research, with data collection from daily field, interview with the class teacher and focus group with the students. After data collection, transcription and analysis were performed. We have identified through the field and bibliographical research that the Traditional Games are still few used as content of EFE mainly in high school, whose predominance is sports. Nevertheless, the research demonstrated the effective possibility of developing them in EFE in High School, as new contents, evidencing that the Traditional Games promote knowledge, cooperation, union among colleagues, and awaken joy, laughter, and will to play more and again